Loco-Regional Treatments for Hepatocellular Carcinoma in People Living with HIV - Cristina Micali; Ylenia Russotto; Grazia Caci; Manuela Ceccarelli; Andrea Marino; Benedetto Maurizio Celesia; Giovanni Francesco Pellicanò; Giuseppe Nunnari; Emmanuele Venanzi Rullo (MDPI AG, 2022)
Hepatocellular carcinoma (HCC) accounts for approximately 75-90% of primary liver cancers and is the sixth most common cancer and the third leading cause of cancer-related deaths worldwide. In the HIV-positive population, the risk of HCC is approximately four times higher than in the general population, with higher cancer-specific mortality than in HIV-negative patients. In most cases, HCC diagnosis is made in patients younger than the HIV-negative population and in the intermediate-advanced stage, thus limiting the therapeutic possibilities. Treatment choice in HIV-positive patients with HCC is subject to cancer staging, liver function and health status, as for HIV-negative and non-HIV-negative HCC patients. There are relatively few studies on the efficacy and safety in HIV-positive patients to date in loco-regional treatments for HCC. So far, literature shows that curative treatments such as radiofrequency ablation (RFA) have no significant differences in overall survival between HIV-positive and HIV-negative patients, as opposed to palliative treatments such as TACE, where there is a significant difference in overall survival. Although it can be assumed that the most recently discovered loco-regional therapies are applicable to HIV-positive patients with HCC in the same way as HIV-negative patients, further studies are needed to confirm this hypothesis. The purpose of our review is to evaluate these treatments, their efficacy, effectiveness, safety and their applicability to HIV-positive patients.